2015
DOI: 10.1177/2333721415607833
|View full text |Cite
|
Sign up to set email alerts
|

Green Care Farms

Abstract: Objective: To explore the value of day services at green care farms (GCFs) in terms of social participation for people with dementia. Method: Semi-structured interviews were conducted with people with dementia who attended day services at a GCF (GCF group, n = 21), were on a waiting list (WL) for day services at a GCF (WL group, n = 12), or attended day services in a regular day care facility (RDCF group, n = 17) and with their family caregivers. Results: People with dementia in the GCF and WL group were prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 35 publications
2
32
0
Order By: Relevance
“…Furthermore, the self-reported quality of life by residents was higher in green care farms compared with regular nursing homes [ 29 ]. Similar findings were found for day care services at green care farms [ 23 , 30 ]. Although various types of small-scale homelike care models exist, there is a lack of theoretical frameworks underpinning components and possible working mechanisms.…”
Section: Introductionsupporting
confidence: 82%
See 1 more Smart Citation
“…Furthermore, the self-reported quality of life by residents was higher in green care farms compared with regular nursing homes [ 29 ]. Similar findings were found for day care services at green care farms [ 23 , 30 ]. Although various types of small-scale homelike care models exist, there is a lack of theoretical frameworks underpinning components and possible working mechanisms.…”
Section: Introductionsupporting
confidence: 82%
“…Originating outside the healthcare sector, green care farms combine agriculture with care activities and aim to enable independence and participation in people with dementia for as long as possible. The rationale of green care farms is that people should be able to participate in daily activities as much as possible and care service delivery is integrated in daily life [ 23 ]. Furthermore, the physical environment (including animals, plants, natural elements) offers many opportunities to incorporate these activities into normal daily care practices.…”
Section: Introductionmentioning
confidence: 99%
“…GE reduces stress, depression and blood pressure, increases self-esteem, mood and wellbeing, and enhances heart rate variability. These benefits seem to be universally obtainable, with evidence of health and wellbeing improvements in children and adolescents [9], adults [1][2][3][4][5][6][7][8] and vulnerable cohorts including disaffected youth [10], adults living with dementia [11] and those experiencing physical and/or mental ill-health such as post-traumatic stress disorders [12]. Wellbeing is important to health because it increases life expectancy, improves recovery from illness [13,14] and is associated with positive health behaviours.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have also found that social farming can provide care to elderly people with mild or severe signs of dementia (De Bruin et al 2009;De Bruin et al 2012;Schols and van der Schriek-van Meel 2006). At the same time these studies have observed a positive level of appreciation from the participants regarding their personal relationships with farmers, the informal-not clinical-context of the activities, and the opportunity to perform a variety of useful activities (De Bruin et al 2015;Hassink et al 2010). In a study by De Boer et al (2016), dementia patients on a social farm were found to be more likely to participate in outdoor activities and green exercise and to engage more in social interactions than those in nursing homes.…”
Section: Introductionmentioning
confidence: 82%